Dechema chemistry data series : liquid - liquid equilibrium data collection 1 Binary systems tables, diagrams and model parameters - Sorensen, J. M.; Arlt, W. (Frankfurt Dechema, 1979)
part 1
Keywords: Liquid-Liquid Equilibrium